CARTOGRAFIAS FRENTE AO DESASTRE-CRIME DA SAMARCO, VALE, BHP BILLITON NO RIO DOCE - Paula de Moreira Guimarães (2018)
This masters dissertation aims to investigate the corporate control strategies over the territory affected by the ongoing crime disaster in the Rio Doce (Doce River) basin, triggered by the rupture of the Fundão dam, owned by Samarco (Vale/BHP Billiton), in Mariana (MG) on November 5, 2015. In this context, it is understood that the collapse of the dam unfolds in multiple fragmentation in the relations between people, ways of life and territory, leading to processes of deterritorialization, that is, the loss of control of some over their living spaces (HAESBAERT, 2004). Such boundaries are often deepened by institutional practices and control policies over reparation processes, that concomitantly, reterritorializes the flows and social and material relations under the business logic, from the articulation of a private disaster management system. Given this context, this masters dissertation intends to map strategies, in order to expose their structure more clearly, aiming to dismantle them in order to guarantee viable exits that strengthen the leadership of those affected in the decision-making spaces. Thus, more than an analytical approach about the subjects and the pre-established phenomena, the problematic under investigation demands the understanding of its dynamic dimension, subsidized by the cartographic method (DELEUZE, GUATTARI, 1995). The results from this investigative process are the understanding of the multiple deterritorializations - socio-spatial and institutional - that make up the corporate control over the affected territory.